Psammechinus miliaris ? (Muller, in Knorr 1771 - Madeira, Patrícia; Kroh, Andreas; Cordeiro, Ricardo; De, António M.; Martins, Frias; Ávila, Sérgio P. (Zenodo, 2019)
Psammechinus miliaris ? (Müller, in Knorr, 1771) Reports for the Azores: non Echinus microtuberculatus Blainville, 1825 —? $ Barrois 1888: 109 [misidentification]; Psammechinus miliaris (Gmelin, 1791) — Mortensen 1927a: 294–295; Nobre 1938: 110–111, figs. 48–49; non Psammechinus microtuberculatus (Blainville, 1825) — Nobre 1938: 111–112 [based on Barrois 1888]; Tortonese 1965: 333–335, fig. 159 [based on Nobre 1938];? $ Castro & Viegas 1983: 24 [misidentification]; Pereira 1997 [based on Barrois 1888]: 334; Haddad & Barreiros 2008: 9; Micael & Costa 2010: 323 [based on Nobre 1938]; Micael et al . 2012: 4 [based on Barrois 1888]; Psammechinus miliaris (M̹ller, in Knorr, 1771)—? $ Mortensen 1943a: 127–139, figs. 56a–b, 57, 58a–b, 59a, 60b, 63b, pl. 10, figs. 3–5, pl. 18, figs. 1–7, 20–21, pl. 58, figs. 19, 23– 25; Moyse & Tyler 1995: 680, 12.8; Schultz 2006: 198–198, figs. 370–372; Micael & Costa 2010: 323; Micael et al . 2012: 4. See: Mortensen (1943a); Schultz (2006). Occurrence: Northeast Atlantic, from Iceland and Scandinavia (Mortensen 1903) to Cape Blanc (Mortensen 1925, Nobre 1938), including the?Azores (Barrois 1888),?Madeira (Jesus & Abreu 1998),?Canaries and? Cape Verde (Tortonese 1965). Depth: 0–100 m (Mortensen 1927a);? AZO: 10–20 m (Barrois 1888). Habitat: virtually any kind of bottom (on bouldery sheltered shores, among sea-grass or algae, under stones, on rocks; Picton 1993); omnivorous, depending on the bottom on which it lives (Mortensen 1943a). Larval stage: planktotrophic (Emlet 1995). Commercial value: edible (Lawrence, J.M. 2007). Remarks: Psammechinus microtuberculatus (Blainville, 1825) was frequently reported from the Azores, unfortunately without descriptions. Koehler (1921b) showed some concerns about the records for the Atlantic, since he believed that the geographical range of this species did not go further than the Iberian Peninsula. Mortensen (1927b, 1943a) stated that the species Psammechinus microtuberculatus was endemic to the Mediterranean Sea and all ...